Tra sociologia del linguaggio e società digitale, S. Capogna, Eurilink University Press, 2021 - Delli Poggi, Bianca (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
Stefania Capogna’s book offers an innovative reflection on the centrality of language and its constitutively social nature. The main objective is to attempt to define the theoretical framework, basic principles and essential notions by means of which language can be analysed in its functions and social implications.